A Plasminogen Activator Inhibitor-2 from a Promyelocytic Leukemia Cell Line, PL-21, Binds to the Carboxy-Terminal Chain of Plasminogen Activators - Takeuchi, Tetsuo; Niiya, Kenji; Kubonishi, Ichiro; Miyoshi, Isao (Thrombosis and Haemostasis, 1990)
A promyelocytic leukemia cell line, PL-21, was found to produce an inhibitor of plasminogen activators (PAI). The PAI reacted to anti-PAl-2 but not anti-PAI-1 anti-serum and had an apparent molecular weight of 43 kDa on unreduced SDS-PAGE. The PAI inhibited not only urokinase-type plasminogen activator (u-PA) but single- and two-chain tissue-type plasminogen activators (t-PAs) on plasminogen-containing fibrin plate. It formed SDS-stable complexes with both t-PA and u-PA but not with prourokinase as demonstrated by both fibrin zymography and immunoblotting using anti-PA and anti-PAI-2 antisera after SDS-PAGE. These complexes were still present even after reduction with dithiothreitol. The PAI appears to bind to the carboxy-terminal chain of both PAs, because the part of the band corresponding to the carboxy-terminal chain of PAs moved to an upper position as a result of complex formation when two-chain form of PAs were incubated with the PAI and analyzed by SDS-PAGE followed by immunoblotting